Analisis Kinerja Keuangan Menggunakan RGEC Terhadap Nilai Perusahaan (Studi pada Perbankan yang Listing di BEI Tahun 2015-2019) - Linda, Linda; Suhardi, Dadang; Komarudin, Munir Nur; Maulana, Yasir (Universitas Kuningan, 2021)
The purpose of this study was to determine the effect of risk profile, good corporate governance, earning and capital on firm value. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling method used is purposive sampling. The number of samples used as many as 26 companies from a population of 43 companies. This research data is in the form of secondary data. The data collection technique used in this research is documentation. The analysis technique used is panel data regression. The results of this study indicate that risk profile, good corporate governance, earning and capital simultaneously affects firm value. Meanwhile the partial test results show that risk profile has a positive effect on firm value, good corporate governance has no positive effect on firm value, earning has no positive effect on firm value, and capital has a positive effect on firm value.